Pengaruh Pemahaman Aturan Pajak Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Perusahaan Manufaktur Elektronik Elektrik Di Kawasan EJIP Yang Tergabung Dalam Anggota Serikat FSPMI) - Imam Hadiyanto (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2024)
This study aims to analyze the relationship between understanding tax rules and tax socialization on individual taxpayer compliance in the Electronic Electrical Manufacturing Company located in the EJIP Area of ​​South Cikarang and affiliated with the FSPMI union. The method used is a quantitative research design with data collection through questionnaires, literature studies, and internet research. The sample was taken using a purposive sampling method from a population of 37,000 taxpayers, with 100 respondents who were individual taxpayers from 18 companies registered with the KKP of South Cikarang. Data analysis was carried out using descriptive and regression analysis, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results of the study indicate that partially, both understanding tax rules and tax socialization have a positive and significant effect on taxpayer compliance. Simultaneously, these two variables are also proven to have a significant effect on individual taxpayer compliance at the research location. This finding confirms the importance of understanding and socialization of taxation in increasing the level of taxpayer compliance.